Synthesis of nanostructure mixed oxides CeO2-Al2O3 by the gel combustion method - Dai, Luu Minh; Nhiem, Dao Ngoc; Phu, Nguyen Van; Lim, Duong Thi (Vietnam Journal of Chemistry, 2012)
The nanostructure mixed oxides powder CeO2–Al2O3 has been synthesized by the combustion of gel from polyvinyl alcohol (PVA) as polymer basic and mixture metal nitrate at 850oC for 2 hours. Characterization of mixed oxides powder CeO2–Al2O3 was determined by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and specific surface area analysis from N2 adsorption data at 77 K by Brunaure Emmet Teller (BET) method. The gel combustion method was a successful method with short time for synthesis, available raw materials and without special equipment. The simple phase of mixed oxides powder CeO2–Al2O3 were obtained from thermal treatment at 850oC for 2 hrs. The optimum conditions of synthesis method: (Al3++Ce4+)/PVA molar ratio = 1:3, Ce4+/Al3+ molar ratio = 5/5, pH = 4, gel formation temperature at 80oC. Samples synthesized under optimal conditions has average crystalline size < 50 nm with large specific area of about 87.5 m2/g. The effects to structure, property of mixed oxides powder CeO2-Al2O3 as calcining temperature, gel formation pH and Ce4+/Al3+ molar ratio have been studied.